(untitled) (Proceedings of the International Conference on Public Health, 2017)
Smoking is a bad habit that danger the smoker and the non-smoker. In SMKN 2 Bandar Lampung, some amounts of students, have started smoking. Therefore, it is urgent to conduct socialization and found anti-smoking. We proposed to form agents (name of agent is Mr. Narsis) to rehabilitation for smoking students that aimed to educate students about danger of smoking and delegate the students of SMKN 2 Bandar Lampung will be anti-smoking representatives who understand and able to do socialization, management, and rehabilitation for smoking students as the solution to create a healthy environment in school. The method is agents were selected from qualified participants of socialization. The selected students will go through counseling training and become peer counselor for their smoker friends. There will be 50 agents who will be divided into 17 groups, each group will counsel 5 active smoker. There were three simulations conducted with three different skills of counselor in each simulation. Another method used is snake and ladder game about anti-smoking campaign. Finally, there were three evaluations, in pre-socialization, after socialization, and the overall skills of anti-smoking counselor. The result from this program is will be form agents anti-smoking as counselor and decrease smokers at school